Randomised phase III trial of FEC120 vs EC-docetaxel in patients with high-risk node-positive primary breast cancer: final survival analysis of the ADEBAR study - Janni, Wolfgang; Wischnik, Arthur (British journal of cancer, 2016)
Background: Taxane-containing adjuvant chemotherapy has been established as standard treatment in node-positive breast cancer. This study compared efficacy and tolerability of epirubicin (E)/cyclophosphamide (C) followed by docetaxel (Doc) with a dose-dense 5-fluorouracil (F)+E+ C regimen. Methods: The ADEBAR study was a randomised phase III trial for women with primary invasive breast cancer and ≥4 metastatic axillary lymph nodes (n=1364). Treatment consisted of four 21-day cycles of E plus C, followed by four 21-day cycles of Doc (EC-Doc), or six 28-day cycles of E plus F plus C (FEC120). Results: Disease-free survival (DFS) was similar in the two treatment arms as shown by multivariate Cox regression adjusted for other prognostic factors (EC-Doc vs FEC120, hazard ratio (HR): 1.087; 95% confidence interval (CI): 0.878-1.346, P=0.444). In addition, there was no significant difference in overall survival (OS) between the two groups (HR: 0.974; 95% CI: 0.750-1.264, P=0.841). Haematologic toxicity was more common in FEC120 recipients; non-haematologic toxicities occurred more frequently in the EC-Doc arm. The serious adverse event rate was significantly higher in the FEC120 group (29.7% vs 22.5%). Conclusions: EC-Doc provides a feasible and effective alternative therapy option to FEC120 with a different safety profile in this high-risk breast cancer cohort.